Doping in perovskite nanocrystals, perovskite solar cells with organic carrier transport layers, and Selenium solar cells - Liu, Wenbo (Nanyang Technological University, 2021)
Perovskite materials are materials with the perovskite structure ABX3 (X=Cl, Br, I). Perovskite nanocrystals (PNCs) and perovskite bulk materials are studied in this thesis. The synthesis of PNCs under high temperature is studied firstly. A modified method that applies metal acetate and halogen acid as the separated B and X source was presented. Cations (Zn2+, Sn2+, and Mg2+) and anions (Cl-) were added into the precursor to study their influence on the Mn emission intensity of Mn-doped PNCs. The nucleation processes of doped PNCs were investigated at the same time. The Mn and Zn co-doped PNCs have been used as phosphors in the down-conversion light-emitting devices (LEDs). Perovskite solar cells (PSCs) based on perovskite bulk materials have made remarkable progress in recent years. Nevertheless, the scientific significance of PSCs goes far beyond the simple pursuit of efficiency. PSCs can serve as a very good platform to try organic carrier transport materials and promote the development of organic semiconductors. Here, a series of small molecule organic materials with varied functional side chains have been applied as the electron transport layers (ETL) for perovskite materials. The morphology, internal aggregation of small molecule organic materials on the ITO/ poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT: PSS)/Perovskite layer substrate have been investigated, their influences on the device performance have been discussed. Next, the interactions between the perovskite surface and organic transport layers are studied. A well-designed polymer has been applied as the hole transport layer(HTL) of PSCs. The side chains of this specific polymer could passivate the perovskite surface to improve the fill factor and stability of fabricated PSCs. Since the lead (Pb)-containing PSCs is not friendly to the environment and the perovskite materials used in PSCs is not stable, it is necessary to explore the next generation of photovoltaic materials. Se absorber is nontoxic and stable under ambient conditions, which is a promising photovoltaic material. Se solar cells (SSCs) based on the SnO2 ETLs and polymeric HTLs has been fabricated. The aging dynamic of SSCs has been studied. The study of doped PNCs helps to deepen the understanding of the nucleation process of PNCs. A variety of organic materials were used as the carrier transport layer of PSCs, which provides a reference for designing new functional molecules. The fabricated SSCs have excellent stability, which can be further modified and used in harsh environments.